An IoT-Based Motorcycle Security System Using Arduino and Android for Theft Prevention - Rakhmadi, Aris; Aji, Doni Kurnia; Rosad, Safiq; Azis, Abdul; Wahyusari, Retno (Compiler, 2025)
Motorcycle theft remains a prevalent issue, especially in urban areas, where traditional security measures such as mechanical locks and ignition keys are easily bypassed. This research presents an IoT-based motorcycle security system integrating Arduino, Bluetooth communication, and an Android application to enhance theft prevention. The system employs an Arduino Uno microcontroller, HC-05 Bluetooth module, and SW-420 vibration sensor to detect unauthorized access and trigger security mechanisms. Users can remotely monitor and control their motorcycles via an Android application, which allows engine immobilization and alarm activation functions. The system was tested for hardware performance, Bluetooth connectivity, and software reliability. Results indicate that Bluetooth communication remains stable within a 10-meter range, the vibration sensor effectively detects unauthorized movements, and real-time commands between the application and Arduino execute with minimal latency. Cost analysis suggests that the system, with a total hardware cost of Rp 223,000, is an affordable and effective solution for motorcycle security. Despite some range limitations, the study demonstrates the feasibility of IoT-based security enhancements. Future improvements include GPS tracking and GSM communication for extended monitoring. This research contributes to developing innovative, cost-effective, and user-friendly vehicle security solutions.